ANÁLISE DA MATÉRIA ORGÂNICA DISSOLVIDA EM EFLUENTES DE ABATEDOURO BOVINO UTILIZANDO ESPECTROSCOPIA DE FLUORESCÊNCIA E PARAFAC - MURILLO CRUZ MATOS (2022)
The present work aimed to evaluate the Dissolved Organic Matter (DOM) in effluents generated from a slaughterhouse industry at different stages of the effluent treatment process as well as in water body receiving effluent by using fluorescence spectroscopy technique associated with the canonical polyadic/parallel factor analysis (PARAFAC) and Principal Component Analysis (PCA). Dissolved Organic Carbon (COD), Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD) and humification index were also determined. The analyzed samples were collected in Onça stream and a slaughterhouse called “Slaughterhouse Esperança” located in the state of Mato Grosso do Sul, Brazil, throughout 2021, in the four seasons of the year. The samples were collected in four sites: two effluent treatment plants, (i) entrance and (ii) exit of slaughterhouse wastewater; and two water bodies at Onça Stream, (iii) upstream and (iv) downstream. The DOM of the residual water at the entrance and exit sites of the slaughterhouse treatment system was shown to be composed mainly proteins, chlorophyll and in less extend of humic substance, while in the receiving water body it was mainly constituted humic substances. Particularly, the decrease of COD, BOD and COD parameters at exit, compared to the entrance site, confirms the biodegradation of the organic matter by microorganisms in more humified compounds at the biological lagoons that corroborate with the results obtained by fluorescence spectroscopy. The biological and humification indices for obtained by fluorescence spectra, for the Onça Stream no show differentiation at the upstream and downstream sites, those results corroborate by the physical-chemical and PARAFAC analyzes. Therefore, the fluorescence spectroscopy together with multivariate analysis (PARAFAC and PCA) proved to be a viable tool for evaluating the quality of DOM in slaughterhouse wastewater.